Tracing the Trajectory of Accounting Information Research for Managerial Decision-Making: A Bibliometric and Science Mapping Analysis - Mirna Triana; Rima Rachmawati; Herry Achmad Buchory; Andry Arifian Rachman; Rita Yuniarti (Yayasan Edukasi Cakrawala Nusantara, 2026)
This study examines the dominant themes and emerging trajectories of accounting information for managerial decision-making using bibliometric analysis and science mapping. The data were retrieved from the Scopus database, which covers 626 publications published between 2010 and 2025. Biblioshiny and VOSviewer were used to map publication trends, author productivity, country contributions, leading journals, and keyword co-occurrence patterns. The findings show a marked increase in research output after 2022, reaching 93 publications by 2025. The United States and China were the leading contributing countries, whereas Pamucar D was the most prolific author. The most prominent publication outlets were Expert Systems with Applications, Journal of Cleaner Production, and IEEE Access. Keyword analysis reveals a growing convergence among decision support systems, artificial intelligence, and management accounting tools, indicating a shift toward data-driven and technology-enabled managerial decision-making. These findings provide a structured overview of the thematic evolution of the field and future research directions.